2019
DOI: 10.1075/is.18001.sze
|View full text |Cite
|
Sign up to set email alerts
|

The perception of a robot partner’s effort elicits a sense of commitment to human-robot interaction

Abstract: Previous research has shown that the perception that one’s partner is investing effort in a joint action can generate a sense of commitment, leading participants to persist longer despite increasing boredom. The current research extends this finding to human-robot interaction. We implemented a 2-player version of the classic snake game which became increasingly boring over the course of each round, and operationalized commitment in terms of how long p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…In the context of human-human interaction, several studies provide support for this general hypothesis i.e., that the perception of a partner's effort elicits a sense of commitment, leading to increased effort, persistence and performance on boring and effortful tasks ( [10], [11], [12]). Building on this, in [13] the authors have recently found evidence that the perception of a robot partner's apparent investment of cognitive effort boosted people's persistence on a boring task which they performed together with a robot.…”
Section: A Related Researchmentioning
confidence: 96%
“…In the context of human-human interaction, several studies provide support for this general hypothesis i.e., that the perception of a partner's effort elicits a sense of commitment, leading to increased effort, persistence and performance on boring and effortful tasks ( [10], [11], [12]). Building on this, in [13] the authors have recently found evidence that the perception of a robot partner's apparent investment of cognitive effort boosted people's persistence on a boring task which they performed together with a robot.…”
Section: A Related Researchmentioning
confidence: 96%
“…Recent evidence shows that a number of elements influence our actions, cognition and emotions during HRIs. These include the motivational factors underpinning an interaction with a robot, such as a sense of commitment to a robot by the user [110], or our perception of robots making an effort during interaction [111]. An important avenue for future research will be to explore more deeply whether elements that drive our motivation to engage with a robot are related to our cognitive styles and culturally derived preferences.…”
Section: Future Perspectives On Developing Culturally-attuned Robotsmentioning
confidence: 99%
“…This example generalizes to other contexts where one's losing focus on a joint action owing to overestimation of a robot's capabilities may entail a high risk. A human agent's lack of commitment to a joint task in a factory with a robot partner might lead that human to become uninterested or to lose focus [38]. In certain industrial contexts, this holds risks relating to potential injury to the person or damage to the robot, especially because workers are increasingly working in closer contact with their robot partners [39,40].…”
Section: When?mentioning
confidence: 99%
“…For cognitive effort, for instance, one might feasibly take some measure of an interactor's cognitive load over the course of a task. This is because [28,29,38] cognitive effort investment [29,38] directly sustains an agent's motivation to contribute to a joint action retail shops autopilot systems [37] increases predictability of an increase in one's cognitive effort should presuppose an increase in cognitive load. This presents a complication because one of the principal ways in which cognitive load is measured is through pupillometry [71][72][73][74], which is a difficult variable to measure in conditions that are not very tightly controlled.…”
Section: How?mentioning
confidence: 99%
See 1 more Smart Citation